Production sharing contracts in Indian oil & gas sector - Pandey, Ajay ([London] : SAGE, 2016)
The case describes the policies followed by the Indian government to attract private investments for oil & gas exploration. This case is based around observations made by the Comptroller and Auditor General of India on some of the petroleum sharing contracts and the remedial measures suggested by a committee appointed by the government.
Originally Published in: Pandey, A. (2014). Production Sharing Contracts in Indian Oil & Gas Sector. PSG0115. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Investments -- India -- Case studies; Energy industries -- Finance -- Case studies; Corporations -- Finance -- Case studies; Production management -- Case studies; Contracts -- India -- Cases; India -- Economic policy -- Case studies